Comparing the effectiveness and safety of Dinoprostone vaginal insert and double-balloon catheter as cervical ripening treatments in Chinese patients - Yan, Jinjing; Yin, Baomin; Lv, Hanghang (Frontiers in Medicine, 2022)
Background: This retrospective study was to compare the effectiveness and safety of Dinoprostone vaginal insert versus double-balloon catheter as cervical ripening agents for labor induction. Methods: Pregnant women with Bishop score < 7, who received either Dinoprostone vaginal insert 10 mg or Cook’s double-balloon catheter for labor induction, were studied. The primary outcome was the rate of vaginal delivery within 48 h; the secondary outcomes were the proportion of women undergoing cesarean section, labor duration, oxytocin administration, changes in Bishop score, complications during labor, and maternal/neonatal outcomes. Results: 182 women were included in Dinoprostone group, and 199 women were in double-balloon catheter group. The rate of vaginal delivery within 48 h was significantly higher in Dinoprostone group than that in double-balloon catheter group (90.11 % vs. 75.38 %, P=0.0002). There were 18 cesarean section deliveries (9.89 %) in Dinoprostone group and 49 cesarean section deliveries (24.62 %) in double-balloon catheter group, with significant differences between two groups (P=0.0002). The duration of labor was higher in Dinoprostone group, while the augmentation with oxytocin was significantly lower in Dinoprostone group than in double-balloon catheter group (all P<0.0001). The incidence of chorioamnionitis was significantly higher in double-balloon catheter group as compared with Dinoprostone group (0 vs 12, P=0.0005), while neonatal outcomes were similar in two groups. Conclusion: Dinoprostone vaginal insert as cervical ripening agent is more effective for labor induction and with lower risks of chorioamnionitis as compared with double balloon catheter in Chinese populations.